Manuel Martí o la legitimación del documento epigráfico - Hernando Sobrino, María del Rosario (Cuadernos de Filología Clásica. Estudios Latinos, 2007)
The aim of this paper is to emphasize the work developed by Manuel Martí in the field of Epigraphy, showing how his new conception of the epigraphic document as well as the methodological bases established by him were the premises that made possible the turn experienced by the epigraphic investigation during the Spanish Enlightenment.